Rancang Bangun Sistem Informasi Laboratorium Klinik Berbasis Web Pada Laboratorium Klinik Utama SAFIRAH Sidoarjo - Andriyas, Mohammad; Sukmaaji, Anjik; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
This Safirah clinical laboratories in the ministry received a lot of medical tests, but in its information systems are not going well, the medical personnel often face a variety of administrative problems. The problem that often occurs is a problem receiving transactions patient, patient examination transaction, the transaction ordering reagents, reagent revenue transactions in its report that while earnings reports and summary reports doctors. Besides, have not been well integrated inter-section in the clinical laboratory. Based on the above problems, clinical laboratories safirah require an application or system capable of handling administrative problems correctly and quickly. This application is also capable of integrating between the administration and the manager very well. From the results of tests and evaluations that have been done, the system can be built to handle the administration of data processing that has been integrated between the administration and the manager very well and this system can provide regular reports so that managers can make the evaluation of each end of the month or the end of the year. Keywords: Clinical laboratory, Web Design Application, clinical laboratory information system